Administrative responsibility for violations of legislation in the field of employment of the population - Hryshyna, Nataliia; Rostovska, Karyna (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2023)
To date, the level of unemployment, which is associated with the termination or limited format of work of enterprises, institutions and organizations, is significant. This indicates the need for the formation of an effective state policy in the field of employment, an effective model of combating unemployment and the expansion of employment assistance programs. The issue of administrative responsibility in the field of public employment deserves special attention. According to the Law of Ukraine "On Employment of the Population", employment is the activity of individuals not prohibited by law, related to the satisfaction of their personal and social needs with the aim of receiving income (wages) in monetary or other form, as well as the activities of members of one family, who carry out economic activities or work for business entities based on their property, including free of charge. Everyone has the right to a freely chosen employment. Forced labor in any form is prohibited. Voluntary unemployment of a person cannot be the basis for bringing him to responsibility. Employment of the population is ensured by establishing relations regulated by labor agreements (contracts), conducting business and other types of activities not prohibited by law.